Kajian Pengembangan Kurikulum Maritim dalam Menumbuhkan Rasa Cinta Bahari Siswa - Muhamad Faiz Prasetia; Enok Maryani; Mamat Ruhimat (Jurnal Penelitian Pendidikan Geografi, 2024)
This research is carried out in order to study the development of ideas or curriculum policies in the field of maritime which is indeed a need of the public in particular who reside in the northern coastal area of Subang County This curriculum is an effort to support one of Indonesia's dreams of becoming the largest archipelagic country and the World Maritime Poros. The maritime curriculum program is a policy that aims to introduce the potential of maritime affairs and fisheries in Indonesia's coastal areas to the younger generation, in order to awaken the spirit of love for the sea in coastal communities, especially for students in coastal schools. The research method used is the study of literature studies of articles, journals and references related to the Maritime Curriculum and observasion, data analysis techniques using qualitative descriptive type. Based on the results of the research, the development of this maritime curriculum resulted in five indicators, including: 1) a marine-based curriculum; 2) curricular content based on community life patterns; 3) a problem-solving curricule; 4) student skills development; and 5) public participation.